Comparative Analysis of Green Banking Implementation in Mitigating Financing Distribution Risk between Bank Syariah Indonesia and Bank Rakyat Indonesia - Pratomo, Dimas; Kurniawan, Muhammad; Handayani, Nur Fitri (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: In the distribution of financing, the implementation of green banking is outlined in green finance, which is one of the financing schemes or lending to environmentally friendly businesses. Green finance activities focus on risk mitigation in providing financing to sustainable development projects by considering the impact that these projects will have. Objectives: This research aims to find out how the application of green banking implementation analysis mitigates the risk of financing distribution. Method: This research is qualitative research of descriptive type. The data sources in this study are the BSI and BRI Sustainability Reports for the 2021-2022 period. The data collection technique used is the library method. Results: The results of this study are seen based on a comparative study conducted between Bank Syariah Indonesia and Bank Rakyat Indonesia, there are differences and similarities between the two banks. One of the differences between the two banks lies in terms of bank monitoring of the company being financed, BSI monitors its business once every three months while BRI monitors it once a year. In addition, there are also similarities between the two banks, one of the similarities between the two banks lies in providing financing to palm oil companies that must have ISPO or RSPO certificates before financing. Implications: This research is expected to provide implications for the green banking program implemented by Bank BSI and Bank BRI in mitigating the risk of financing distribution to customers. Both banks can complement each other to complement the shortcomings in their respective sectors.